Vaginal Duplication Cyst – A Rare Isolated Anomaly Masquerading as a Colonic Duplication Cyst - Simmi K. Ratan; Harsh Bhomaj; Nitin Jain; Sheetal Upreti; Md. Fahim Ahmad; Shramana Mandal; Mehak Sehgal; Rashi Garg (Journal of Indian Association of Pediatric Surgeons)
Vaginal duplication cysts are rare congenital anomalies, especially in pediatric patients, often mimicking other pelvic cystic lesions. We report a 2-month-old female with a lower abdominal lump, urinary retention, and defecation issues. Imaging suggested a rectal duplication cyst, but laparoscopy revealed a vaginal duplication cyst adherent to the posterior vaginal wall. Surgical excision confirmed the diagnosis, and the child had complete symptom resolution. This case emphasizes the rarity of vaginal duplication cysts in infancy and the importance of surgical management for definitive diagnosis and treatment.